Remifentanil Preconditioning Attenuates Hepatic Ischemia-Reperfusion Injury in Rats via Neuronal Activation in Dorsal Vagal Complex - Cui Cui; Fang Yu; Suqing Yin; Yuting Yang; Yingfu Jiao; Chiwai Cheung; Xiaomin Wang; Bo Qi; Yaling Liu; Peiying Li; Weifeng Yu; Jie Xiao; et al. (Hindawi Limited, 2018)
Remifentanil, an ultra-short acting opiate, has been reported to protect against hepatic ischemia-reperfusion injury, which is a major cause of postoperative liver dysfunction. The objective of this study was to determine whether a central vagal pathway is involved in this protective procedure. Rat models of hepatic ischemia-reperfusion were used in the experimental procedures. The results revealed that intravenous pretreatment with remifentanil decreased serum aminotransferases and hepatic histologic damage; however, an intraperitoneal injection of μ-opioid receptor antagonist did not abolish the protection of remifentanil preconditioning. c-Fos immunofluorescence of the brain stem showed that dorsal motor nucleus of the vagus was activated after remifentanil preconditioning. Moreover, serum alanine aminotransferase, histopathologic damage, and apoptosis decreased in remifentanil preconditioning group compared to vagotomized animals with remifentanil preconditioning, and there was no statistical difference of TNF-α and IL-6 between NS/Va and RPC/Va groups. In addition, remifentanil microinjection into dorsal vagal complex decreased serum aminotransferases, inflammatory cytokines, and hepatic histologic injury and apoptosis, and these effects were also abolished by a peripheral hepatic vagotomy. In conclusion, remifentanil preconditioning conferred liver protection against ischemia-reperfusion injury, which was mediated by the central vagal pathway.